Efficacy and Safety of the Factor VIII/von Willebrand Factor Concentrate, Haemate-P/Humate-P: Ristocetin Cofactor Unit Dosing in Patients with von Willebrand Disease - Lillicrap, D.; Poon, M.-C.; Walker, I.; Xie, F.; Schwartz, B.A.; members of the Association of Hemophilia Clinic Directors of Canada (Thrombosis and Haemostasis, 2002)
The present study was initiated to evaluate the safety and efficacy of Haemate-P® (Humate-P® in North America) (anti-hemophilic FVIII/VWF complex [human] dried, pasteurized) dosed in ristocetin cofactor units (VWF:RCo) in the treatment of von Willebrand disease (VWD) patients in Canada. This retrospective data collection reviewed the medical records of VWD patients treated under the Canadian Emergency Drug Release Program from November 22, 1991, to April 30, 1996. Data collection was accomplished by on-site retrieval from source data for 97 patients. Dosing was based on the German package insert, which lists only Factor VIII:C (FVIII:C) units, which were converted in the study analysis to VWF:RCo units based on the analysis of the individual manufactured lots of product used in these patients (average ratio of 2.6 IU VWF:RCo per IU FVIII:C). Twenty five different lots of Haemate-P/Humate-P were used to treat 437 different events in the 97 study patients (344 hemorrhagic events, 73 surgical interventions and 20 prophylactic infusion cycles). Overall, the median dose of concentrate per infusion used to treat surgical events was 69.1 IU VWF:RCo/kg (range 11.9-222.8); bleeding events 55.3 IU VWF:RCo/kg (range 17.1-227.5) and prophylaxis 41.6 IU VWF:RCo/kg (range 34.6-81.0). Treatment periods varied, with the majority of events treated for ≤ 10 days (91%). Fifty percent of events that were treated longer than 10 days were given for prophylactic reasons. Efficacy was determined in a standardized manner by the physician, based on dosing in VWF:RCo activity. An overall clinical result of “excellent” or “good” was reported in 97% (424/437) of treatment events. A pediatric sub-population analysis of the patient population reported “excellent/good” efficacy in 100% (17/17) of treatment events in infants, 95% (155/164) in children, and 94% (76/81) in adolescent patients. Related adverse events (AEs) were observed in only 4 (4%) patients and were not deemed to be serious. The findings in this study confirm the safety and efficacy of Haemate-P/Humate-P using VWF:RCo dosing in pediatric and adult patients with various types of VWD.
Keywords: von Willebrand disease; Haemate-P/Humate-P; ristocetin cofactor units